تكنولوجيا المعلومات ودورها في دعم القرارات التسويقية على مستوى المؤسسات الجزائرية - بن العايش, فاطمة; معيوف, هدى (جامعة الوادي - University of Eloued, 2022)
This study aims to highlight the impact of information technologies on the quality of marketing decisions in some Algerian institutions, and for this we relied on the descriptive approach and the statistical method to measure this effect. With rapidly changing competition, businesses need to make marketing decisions quickly or risk losing their competitive advantage. The use of information technology allows companies to collect, analyze and use large amounts of customer information. This information is used to reduce risk and uncertainty in decision-making and to maximize the profitability of marketing activities. The study concluded that the senior management of the Algerian institutions studied rely on marketing information when developing marketing plans and making marketing decisions, with the availability of skills to use marketing information technologies.
Information technology and its impact on marketing decision support at the level of Algerian economic institutions
مقال
Keywords: تكنولوجيا المعلومات ; القرارات التسويقية ; بعض المؤسسات الجزائرية